2018
DOI: 10.1186/s12885-018-4180-5
|View full text |Cite
|
Sign up to set email alerts
|

CD31 and VEGF are prognostic biomarkers in early-stage, but not in late-stage, laryngeal squamous cell carcinoma

Abstract: BackgroundPatients suffering from squamous cell carcinoma of the larynx (LSCC) with lymphatic metastasis have a relatively poor prognosis and often require radical therapeutic management. The mechanisms which drive metastasis to the lymph nodes are largely unknown but may be promoted by a pro-angiogenic tumor microenvironment. In this study, we examined whether the number of microvessels and the expression level of vascular endothelial growth factor (VEGF) in the primary tumor are correlated with the degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 38 publications
2
49
0
Order By: Relevance
“…Their deficit reduced angiogenesis and suggested as a probable reason for tumorigenesis inhibition by age [5]. This suggestion is in concordance with higher survival patients with lower presence of vascular endothelial growth factor (VEGF) in a growing tumor of early stages T1-2 [46]. The young lymphoid descendants may be committed (aimed) also toward injured tissues needed for reparation [47] [48].…”
Section: Natural Tissue Growth and Lymphopoiesismentioning
confidence: 69%
“…Their deficit reduced angiogenesis and suggested as a probable reason for tumorigenesis inhibition by age [5]. This suggestion is in concordance with higher survival patients with lower presence of vascular endothelial growth factor (VEGF) in a growing tumor of early stages T1-2 [46]. The young lymphoid descendants may be committed (aimed) also toward injured tissues needed for reparation [47] [48].…”
Section: Natural Tissue Growth and Lymphopoiesismentioning
confidence: 69%
“…Recurrent LSCC in the setting of previous radiation or chemoradiation represents an aggressive disease with significant treatment related morbidity [8,[24][25][26][27]. While there has been significant focus on understanding the genomic landscape of primary laryngeal squamous cell carcinoma [28][29][30][31][32][33][34], few studies have explored molecular signatures of recurrent disease [13,[15][16][17]. Here we present results from a recurrent laryngeal carcinoma cohort with targeted sequencing and transcriptome data that identified multiple pathways predictive of survival independent of clinical variables.…”
Section: Discussionmentioning
confidence: 96%
“…Under this circumstance, some researchers have studied the biomarkers of LSCC. Weller et al reported that CD31 and vascular endothelial growth factor (VEGF) are prognostic biomarkers [7]. Other studies indicated that miR-93-5p [8] and miR-196b [9] are potential markers in LSCC.…”
Section: Introductionmentioning
confidence: 99%